2011
DOI: 10.1609/aimag.v32i2.2336
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Transfer to American Football: From Observation of Raw Video to Control in a Simulated Environment

Abstract: Automatic transfer of learned knowledge from one task or domain to another offers great potential to simplify and expedite the construction and deployment of intelligent systems. In practice however, there are many barriers to achieving this goal. In this article, we present a prototype system for the real-world context of transferring knowledge of American football from video observation to control in a game simulator. We trace an example play from the raw video through execution and adaptation in the simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Bricola [25] recognized activities in basketball from player trajectories by segmented the trajectories into tracklets which were matched to codewords using Dynamic Time Warping. Stracuzzi et al [26] recognized group activities in American Football using a labeled dataset of actions and the trajectories were labeled by matching them to the closest in the labeled dataset. Dynamic time warping was used to compare the signals and the features of each aligned point.…”
Section: B Mining Multi-agent/object Trajectoriesmentioning
confidence: 99%
“…Bricola [25] recognized activities in basketball from player trajectories by segmented the trajectories into tracklets which were matched to codewords using Dynamic Time Warping. Stracuzzi et al [26] recognized group activities in American Football using a labeled dataset of actions and the trajectories were labeled by matching them to the closest in the labeled dataset. Dynamic time warping was used to compare the signals and the features of each aligned point.…”
Section: B Mining Multi-agent/object Trajectoriesmentioning
confidence: 99%
“…Li and Chellapa [20] used a spatio-temporal driving force model to segment the two groups/teams using their trajectories. Researchers at Oregon State University have looked at automatically detecting offensive plays from raw video and transfer this knowledge to a simulator [29]. For soccer, Kim et al [16] used the global motion of all players in a soccer match to predict where the play will evolve in the short-term.…”
Section: Related Workmentioning
confidence: 99%
“…We, on the other hand, do not use predefined behavior libraries, and do not provide counter-strategies. Stracuzzi et al (2012) demonstrated a knowledge transfer method by observing videos of American-football in order to control agent players in a game simulator. It included object tracking, dynamic time warping for action recognition, and an Icarus cognitive architecture to infer strategies in the form of rules.…”
Section: Related Workmentioning
confidence: 99%